Implementasi Konsep SMART-Lib dalam Re-desain Interior Perpustakaan Umum Provinsi Sulawesi Selatan - Daniel, Dea Minerva; Thamrin, Diana; Rakhmawati, Anik (Intra, 2018)
Reading interest in Indonesia is needed to be developed by improving the infrastructure and library interior. Advancement in technologies also acts as a contributing factor in the cultural shift from physical collection to virtual ones. As such, the purpose of this project is to introduce technologies and modern cues to the designated library design. The design object is South Sulawesi Public Library and Archived which located in Jl. Sultan Alauddin km 7, Talasalapang, Makassar.The design method of this project adopt the design thinking process by Nielsen Norman which consists of; (1) Understand (Empathize and Define), (2) Explore (Ideate and Prototype) and (3) Materialize (Test and Implement). The project’s concept is SMART-Lib, where SMART-Lib stands for Sociable, Motivating, Adaptable, Refreshing, and Hi-Tech Library. The concept purpose is to present a modern library which supported by innovative technology that inspires and educate the user in the digital age.